2005
DOI: 10.1212/01.wnl.0000166030.05756.9f
|View full text |Cite
|
Sign up to set email alerts
|

A new screening tool for cervical dystonia

Abstract: The Beth Israel Dystonia Screen (BIDS) identifies cervical dystonia with excellent sensitivity and specificity in a family-based sample. The authors recommend the BIDS for family studies, but cross-validation in a population sample is advisable before applying this method to epidemiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Since most patients first seek attention from their primary care providers, this audience seems particularly important. Fortunately, a simple 5 item screening questionnaire is available with high sensitivity and specificity to aid in the diagnosis of CD (14), and video demonstrations of the key features are available through online resources (e.g. www.neurotoxininstitute.com).…”
Section: Discussionmentioning
confidence: 99%
“…Since most patients first seek attention from their primary care providers, this audience seems particularly important. Fortunately, a simple 5 item screening questionnaire is available with high sensitivity and specificity to aid in the diagnosis of CD (14), and video demonstrations of the key features are available through online resources (e.g. www.neurotoxininstitute.com).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the dystonia was rated with the Abnormal Involuntary Movement Scale in the most severely affected limb and the Global Disability Score (table). All other available and consenting family members underwent a telephone interview including the Beth Israel Dystonia Screen (BIDS) (adapted from Saunders-Pullman et al 7 ). If screened positive, the same examinations as described for family members with known dystonia were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Although superior to family history alone, we cannot fully exclude that a case with dystonia was not detected with the BIDS. While the utility of the BIDS as a screening tool was previously described to identify family members with cervical dystonia only, 13 it is a computer-assisted telephone interview designed to detect many forms of dystonia. The present study demonstrated that the BIDS appears to be an excellent screening instrument also for genetic studies of FTSD but further validation is advisable.…”
Section: Patients and Familiesmentioning
confidence: 99%